Usefulness and safety of biliary percutaneous transluminal forceps biopsy (PTFB): our experience. Issue 2 (March 2014) - Ierardi, Anna Maria; Mangini, Monica; Fontana, Federico; Floridi, Chiara; De Marchi, Giuseppe; Petrillo, Mario; Capasso, Raffaella; Chini, Claudio; Cocozza, Eugenio; Cuffari, Salvatore; Segato, Sergio; Rotondo, Antonio; et al.
Abstract Aim: To evaluate the usefulness and safety of percutaneous transluminal forceps biopsy in patients suspected of having a malignant biliary obstruction. Material and methods: Forty consecutive patients (21 men and 19 women; mean age, 71.9 years) underwent forceps biopsy through percutaneous transhepatic biliary access performed to drain bile. Lesions involved the common bile duct (n 8), common hepatic duct (n 18), hilum (n 6), ampullary segment of the common bile duct (n 8) and were biopsied with 7-F biopsy forceps. Final diagnosis was confirmed with pathologic findings at surgery, or clinical and radiologic follow-up. Results: Twenty-one of 40 biopsies resulted in correct diagnosis of malignancy. Thirteen biopsy diagnosis were proved to be true-negative. There were six false-negative and no false-positive diagnoses. Sensitivity, specificity and accuracy in aspecific biliary obstructions were 85%, 100% and 88, 7% respectively. Sensitivity of biopsy in malignancies was higher than in benign obstructions (100% vs 68, 4%, CI = 95%). Sensitivity was lower in the hilum tract and in the common bile duct than in other sites (CI = 95%). No major complications related to biopsy procedures occurred. Conclusions:Percutaneous transluminal forceps biopsy is a safe procedure, easy to perform through a transhepatic biliary drainage tract, providing high accuracy in the diagnosis of malignant biliary obstructions.